The Politeness Principle Actualization in Rodger and Hammerstein’s Drama “King and I” : A Politeness Study - Bustan Hasan; Sudirman Maca; Dahlia D. Moelier (Fakultas Sastra, Universitas Bosowa, 2021)
The aims of the research are to find out and to examine the characters in the drama consider politeness principle when they make dialogue to others, especially in imperative dialogue, politeness types and strategy used by charactersm and factors that influence use of politeness principle. This research is library research by applying qualitative descriptive method and through pragmatic study. By use pragmatic study, the writer has to understand and pay attention well context of the dialogue in the drama. In this study the dialogue of the drama assumed as speech act and characters assumed as speech participant. The writer used Dell Hymes’ theory (1974)to analysis context of the dialogue. The writer also uses politeness principle theory of Geoffrey Leech (1983) and Speech acts theory of J.R. Searle (1969) to analysis the data. The result shows that the characters of the drama consider politeness principle when make imperative dialogue in specific setting. Most of the dialogues indicate applying politeness principle. Strategies that always applied are indirect scale, optionality scale, authority scale and cost-benefit scale. Significant factors that influence and determine the use of politeness principle are social background of participant or character, setting and scene, and end of speech or dialogue.